2014
DOI: 10.1053/j.jvca.2014.04.034
|View full text |Cite
|
Sign up to set email alerts
|

P-Wave Characteristics on Routine Preoperative Electrocardiogram Improve Prediction of New-Onset Postoperative Atrial Fibrillation in Cardiac Surgery

Abstract: Several p-wave characteristics are independently associated with postoperative atrial fibrillation. Addition of these parameters improves the postoperative atrial fibrillation prediction model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…1 The main findings of this work indicated that there were several p-wave characteristics that were associated with postoperative atrial fibrillation with premature atrial contraction, P-wave index, and p-frontal axis all showing independent association.…”
Section: Interatrial Block Is Not a Predictor Of Post-cabg Atrial Fibmentioning
confidence: 67%
“…1 The main findings of this work indicated that there were several p-wave characteristics that were associated with postoperative atrial fibrillation with premature atrial contraction, P-wave index, and p-frontal axis all showing independent association.…”
Section: Interatrial Block Is Not a Predictor Of Post-cabg Atrial Fibmentioning
confidence: 67%
“…); but, these indexes are less readily available and thus more difficult to apply in clinical practice. 12,[33][34][35][36][37] ECG is generally easily accessible and commonly used prior to abdominal surgery, hence, potentially a promising tool for identifying POAF. Upcoming prediction models in abdominal surgical populations should consider including ECG indexes such as PR-interval, P-wave duration and QRS-duration similarly to the model developed by Gu et al for patients undergoing cardiac surgery.…”
Section: Electrocardiogramsmentioning
confidence: 99%
“…La fibrilación auricular (FA) es la arritmia más común, su incidencia es cercana al 60% en pacientes con historia de cirugía cardíaca [4,5]. La FA se encuentra asociada a un incremento en el riesgo de mortalidad, de ingreso a Unidad de Cuidados Intensivos (UCI) y prolongación de la estancia hospitalaria [4].…”
Section: Introductionunclassified
“…La fibrilación auricular (FA) es la arritmia más común, su incidencia es cercana al 60% en pacientes con historia de cirugía cardíaca [4,5]. La FA se encuentra asociada a un incremento en el riesgo de mortalidad, de ingreso a Unidad de Cuidados Intensivos (UCI) y prolongación de la estancia hospitalaria [4]. La alta morbimortalidad atribuida a la FA se deriva del riesgo aumentado de presentar un Accidente Cerebro Vascular (ACV) o un evento tromboembólico como consecuencia de los cambios fisiopatológicos que produce esta condición [5][6][7].…”
Section: Introductionunclassified